You, with a view - Joyce, Jessica (Berkley Romance, 2023)
"Two high school enemies must reunite for a road trip inspired by their grandparents' broken engagement in this electric debut romance. Noelle Shepherd is unemployed, living with her parents, and grieving the loss of her beloved grandmother when she discovers decades-old photos of Gram and a smitten man, tucked alongside a love letter. She creates a TikTok to search for the mystery man, which goes viral, and she's shocked when his grandson responds--a man who happens to be her high school nemesis, Theo Spencer. Noelle refuses to let Theo's annoying accomplishments in adulthood--or his sexy smirk--stand in the way of meeting his grandfather and unlocking the secrets he knew about her gram as a young woman. When she learns that their plans to elope were thwarted, Noelle decides to take the honeymoon road trip they planned but never got to carry out. There's a catch, though: Paul, Theo's grandfather, asks to come with her, and he insists that Theo join them. It'll be a miracle if they make it through the trip without Noelle throwing Theo out of the moving car--or the bed they end up sharing. As the miles tick by, the tension simmers hotter between them ... until she discovers that Theo's hiding a secret that could cause their tenuous relationship to end before it can restart"--